Stress in adolescence: hypothalamic-pituitary-adrenal -axis dysfunctions on behavior, neurochemistry and immune response in rodents - Lima, Ana Paula Nascimento de (2018)
Adolescence is considered one of the critical periods of development and of great relevance to the health of an individual as an adult. Stressor or traumatic events during this period are associated with numerous changes in the development and plasticity of the neuroimmuoendocrine system predisposing the individual to psychiatric disorders. However, studies that investigate neuroimmuno changes related to adolescence are still scarce in the literature. Therefore, the present study sought to evaluate the adult life impacts of two models of stress in adolescence on immune, neurochemical and behavioral parameters in rodents. The studies into this thesis present important results for understanding the HPA axis and how stressors during adolescence modulate the mechanisms involved in the neuroimmuno-endocrine and behavioral response in adult life. Briefly, our results show that stressful situations, during the developmental period of adolescence, homotypic or heterotypic models in a short term (10 -15 days), can be associated with long-lasting changes in neural pathways, behavior and immune parameters, eliciting a potential neuroimmuno-endocrine and behavioral vulnerability for the development of disorders related to stress response in adulthood and also with a greater opportunity to behavioral and physiological flexibility to respond to different environmental and social contexts.